2006
DOI: 10.1002/lt.20660
|View full text |Cite
|
Sign up to set email alerts
|

Living donor liver transplantation for hepatitis C-related cirrhosis: No difference in histological recurrence when compared to deceased donor liver transplantation recipients

Abstract: The question of possible earlier and more aggressive recurrence of hepatitis C virus (HCV) infection after living donor liver transplantation (LDLT) compared to deceased donor liver transplantation (DDLT) remains unanswered. To address this issue we retrospectively reviewed virological, histological, and clinical data in 67 patients (52 DDLT and 15 LDLT) who underwent liver transplant for their HCV-related cirrhosis since April 2001. Our data indicate that there is no statistical difference between LDLT and DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 20 publications
4
25
0
5
Order By: Relevance
“…This was lower than previous studies, 7,10,12,19 where a histologically diagnosed recurrence of chronic hepatitis C occurred in 65 to 90% of HCV positive DDLT recipients GXULQJ WKH ¿UVW \HDUV DIWHU VXUJHU\ ,Q WKH FXUUHQW VWXG\ recurrence occurred within a time range from 3 to 38 months in DDLT group, while in LDLT group, it ranged from 1 to 39 months. This comes in agreement with the study done by Guo et al, 20 where histological evidence of recurrent hepatitis occurred at 4 months and reached 90% 1 year post-LT. In the DDLT group, nine patients showed low viremia, and 19 patients showed high viremia compared to 11 and 20 patients respectively in the LDLT group.…”
Section: Discussionsupporting
confidence: 93%
“…This was lower than previous studies, 7,10,12,19 where a histologically diagnosed recurrence of chronic hepatitis C occurred in 65 to 90% of HCV positive DDLT recipients GXULQJ WKH ¿UVW \HDUV DIWHU VXUJHU\ ,Q WKH FXUUHQW VWXG\ recurrence occurred within a time range from 3 to 38 months in DDLT group, while in LDLT group, it ranged from 1 to 39 months. This comes in agreement with the study done by Guo et al, 20 where histological evidence of recurrent hepatitis occurred at 4 months and reached 90% 1 year post-LT. In the DDLT group, nine patients showed low viremia, and 19 patients showed high viremia compared to 11 and 20 patients respectively in the LDLT group.…”
Section: Discussionsupporting
confidence: 93%
“…However, a prospective controlled trial by Shiffman et al [58] using protocol liver biopsies in 23 LDLT and 53 DDLT found no association between graft type and HCV recurrence in terms of recipient and graft survival or fibrosis progression over 3 years. Guo et al [59] reported similar results from a retrospective study of 15 LDLT and 52 DDLT, with no difference in histological HCV recurrence rates or graft survival over 2 years. Similar short-term results have also been reported by Schmeding et al [60] .…”
Section: Type Of Graftmentioning
confidence: 72%
“…In this study it was noted that 91.1% of the infected individuals are in the chronic phase of the disease. This is worrisome because there is high chance of these individuals evolve to cirrhosis or hepatocellular carcinoma, may be in dicated for liver transplantation in most cases (13) . According to RodriguezLuna et al (21) , HCV recurrence after trans plantation occurs almost in all patients and the evolution of the disease in transplant patients is much faster and more aggressive than in nontransplanted patients.…”
Section: Discussionmentioning
confidence: 99%